THE RELATIONSHIP BETWEEN COFFEE CONSUMPTION HABITS AND THE RISK OF HYPERTENSION AMONG ADOLESCENTS AT SMAN 14 PEKANBARU: HUBUNGAN KEBIASAAN KONSUMSI KOPI DENGAN RISIKO HIPERTENSI PADA REMAJA DI SMAN 14 PEKANBARU - Try Sepriani, Dian; Nurchayati, Sofiana; Rizka, Yulia (Journal of Health and Cardiovascular Nursing, 2025)
Hypertension is no longer a condition limited to adults; it is increasingly observed among adolescents. One suspected contributing factor is the habit of coffee consumption, as coffee contains caffeine, a substance known to affect blood pressure. This study aims to determine the relationship between coffee consumption habits and the risk of hypertension in adolescents. A correlational analytic design with a cross-sectional approach was used. The sample consisted of 95 students from grades 10, 11, and 12 at SMAN 14 Pekanbaru. Data were collected using questionnaires and digital blood pressure monitors. Univariate and bivariate analyses were conducted, with the Spearman Rank test used for bivariate analysis. The results showed that most respondents were 16 years old (36.4%), female (53.7%), and had a moderate coffee consumption habit (61.1%). The Spearman Rank test revealed a significant relationship between coffee consumption and systolic blood pressure (p < 0.000), as well as diastolic blood pressure (p < 0.002). The study concludes that there is a significant relationship between coffee consumption habits and the risk of hypertension in adolescents. It is recommended that adolescents limit their coffee intake to reduce the risk of early-onset hypertension.